Racial discrimination, post-traumatic stress and prescription drug problems among Aboriginal Canadians - Currie, Cheryl (Can J Public Health, 2015)
Objectives: 1) To examine associations between racial discrimination and drug problems among urban-based Aboriginal adults; and 2) to determine whether these associations are best explained by symptoms of psychological stress, distress or post-traumatic stress disorder (PTSD). Methods: Data were collected through in-person surveys with a community-based sample of Aboriginal adults (N = 372) living in a mid-sized city in western Canada in 2010. Associations were examined using bootstrapped linear regression models adjusted for confounders, with continuous prescription and illicit drug problem scores as outcomes. Mediation was examined using the cross-products of coefficients method. RESULTS: More than 80% of Aboriginal adults had experienced racial discrimination in the past year, with the majority reporting high levels in that period. Past-year discrimination was a risk factor for PTSD symptoms and prescription drug problems in models adjusted for confounders and other forms of psychological trauma. In mediation models, PTSD symptoms explained the association between discrimination and prescription drug problems; psychological stress and distress did not. PTSD symptoms also explained this association when the covariance between mediators was controlled. The results also indicate that participation in Aboriginal cultural traditions was associated with increased discrimination. CONCLUSIONS: Most efforts to address Aboriginal health inequities in Canada have focused on the role Aboriginal people play in these disparities. The current findings combine with others to call for an expanded focus. Non-Aboriginal Canadians may also play a role in the health inequities observed. The findings of this study suggest efforts to reduce discrimination experienced by Aboriginal adults in cities may reduce PTSD symptomology and prescription drug problems in these populations.